2012
DOI: 10.5127/jep.024811
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Role of Attention in Mindfulness-Based Cognitive Therapy for Recurrently Depressed Patients

Abstract: Mindfulness-based cognitive therapy (MBCT) has been shown to be efficacious in reducing relapse rate and depressive symptoms in patients with recurrent depression. To date, little is known about the underlying cognitive mechanisms. We investigated the role of attention with the attention network test in a randomized controlled trial with 34 MBCT patients and 37 waiting-list control patients. In the MBCT group depressive symptoms and ruminative thinking decreased and mindfulness skills increased. However, no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
(92 reference statements)
1
13
0
Order By: Relevance
“…Van den Hurk et al (2012) employed a correlational experimental design and found no changes in attentional processes (alerting, orienting and executive attention) or more general attentional functioning in the MBCT group, nor in the waitlist control group. However, the experimental measure of attention (Attention Network Test) employed was used to investigate how fast and how accurately a target stimulus could be detected among alternate cues and stimuli, and as such may not be the most valid measure of attention regulation associated with training in mindfulness meditation.…”
Section: Attention Regulationmentioning
confidence: 96%
“…Van den Hurk et al (2012) employed a correlational experimental design and found no changes in attentional processes (alerting, orienting and executive attention) or more general attentional functioning in the MBCT group, nor in the waitlist control group. However, the experimental measure of attention (Attention Network Test) employed was used to investigate how fast and how accurately a target stimulus could be detected among alternate cues and stimuli, and as such may not be the most valid measure of attention regulation associated with training in mindfulness meditation.…”
Section: Attention Regulationmentioning
confidence: 96%
“…Research has largely supported this notion, and shown that these processes are central components and active ingredients of MBCT. Following MBCT training, participants exhibit improved self-reported mindfulness (4350), reduced rumination (43, 4548, 5153) and worry (43, 47, 53), improved meta-awareness (52, 54, 55), increased self-compassion (56, 57), and reduced emotional reactivity (58). Moreover, these improvements at least partially mediated or predicted the effect of MBCT on treatment outcome (see 5961 for reviews), with the strongest effects found for mindfulness, rumination, worry, and emotional reactivity.…”
Section: Mechanismsmentioning
confidence: 99%
“…Research indicates that MBCT may attenuate these symptoms. MBCT has been shown to reduce overgeneral autobiographical memory (55, 69, 70), improve attention deployment and maintenance during sad mood (71) and reduce attentional-bias towards negative emotional stimuli (72), although such attentional improvements are not ubiquitous (42, 48, 73). MBCT has additionally been shown to augment suppression of currently-irrelevant mental sets (74) and promote both cognitive flexibility and overall cognitive functioning (75), benefits which correlate with a reduction in depressive symptomology.…”
Section: Mechanismsmentioning
confidence: 99%
“…In the present study, where the participating students only had a brief and intensive training in mindfulness, we did not find significant changes in the alerting or orienting subtask of ANT. Findings from van den Hurk et al (2010) and other studies (e.g. Semple, 2010) suggest that enhancements of attention through mindfulness practice may take time to develop.…”
Section: Discussionmentioning
confidence: 75%
“…Higher levels of dispositional mindfulness in psychology students have been found to reduce the extent to which ruminative reactions tend to escalate into self-perpetuating and uncontrollable ruminative cycles (Raes & Williams, 2010). Several studies have found mindfulness practice to reduce rumination (Keune, Bostanov, Hautzinger, & Kotchoubey, 2011;Michalak, Hölz, & Teismann, 2011;van den Hurk et al, 2012). A study examining the effect of mindfulness practice on clinical psychology students found a significant decline in rumination after an 8-week mindfulness intervention (Shapiro et al, 2007).…”
mentioning
confidence: 99%